DPRD dan Otonomi Daerah (Kajian dari Sudut pandang HTN) - Dahlan Thaib (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2001)
The demand of reformation recently has opened the conscienceness of Indonesian people about their political rights that they didn't find and enjoy before, although those all are guaranteed by the constitution of Indonesia. The crowd of the discourse of democracy implementation has invited the participation of people in country organizing whether in the Center (Capital) or in the Territories (Provinces). These all according to the state structure constitution was very gladden for remaining the principle of teaching that open the opportunities to discourse forum to product the consensus to organize the democratic and justice in Indonesia. In territory autonomy contexts, the participation of people through house of territory representatives (DPRD) is very important for the principal that the territory autonomy policy must be put in front of the aspiration and the sake of people.